1996
DOI: 10.1021/cm960133c
|View full text |Cite
|
Sign up to set email alerts
|

Negative Resists Using Acid-Catalyzed Dehydration of Phenylcarbinols:  Correlation between Chemical Structure and Resist Sensitivity

Abstract: A series of phenylcarbinols have been evaluated as components of chemically amplified resists used for KrF excimer laser lithography. The character of the carbon atom to which the hydroxyl group is bonded to determines the insolubilization reactions, leading to differences in sensitivity. Resists using tertiary phenylcarbinol, which converts into polymeric compounds, exhibits the highest sensitivity while the resists using primary phenylcarbinol, which cross-links the phenolic resin, has the lowest sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…[4,5,6] In this article we describe a newly developed resist that uses the ring-chain tautomerism of oacetylbenzoic acid. The formulation, lithographic performance, and insolubilization mechanism of the new resist are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5,6] In this article we describe a newly developed resist that uses the ring-chain tautomerism of oacetylbenzoic acid. The formulation, lithographic performance, and insolubilization mechanism of the new resist are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…We developed negative deep-UV resists based on the polarity change reactions such as pinacol rearrangement, [6,7] phenylcarbinol etherification, [8] and phenylcarbinol dehydration, which have low activation energy compared to acidhardening reactions. [9][10][11] In the course of the development of the deep-UV resists, we found that the resist using phenylcarbinols dehydration exhibited high sensitivity, and small pattern-width dependence on PEB temperature. [ 10] Therefore, we expected that the resist using phenylcarbinols would exhibit a good lithographic performance in terms of sensitivity and CD control.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In the course of the development of the deep-UV resists, we found that the resist using phenylcarbinols dehydration exhibited high sensitivity, and small pattern-width dependence on PEB temperature. [ 10] Therefore, we expected that the resist using phenylcarbinols would exhibit a good lithographic performance in terms of sensitivity and CD control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Also we have reported negative resists that use a cross-linking reaction between a bisazide and a phenolic resin for nanofabrication. [7][8][9] We also discuss the formulation, lithographic performance, and insolubilization mechanism of the new resist. However, the sensitivity of the resist ͑150 C/cm 2 at 50 kV͒ is still not sufficient for efficient fabrication of nanostructures.…”
Section: Introductionmentioning
confidence: 99%